Porous spherical gold nanoparticles via a laser induced process. Issue 19 (2nd September 2022) - Schmidl, Gabriele; Raugust, Marc; Jia, Guobin; Dellith, Andrea; Dellith, Jan; Schmidl, Frank; Plentz, Jonathan
Abstract : Nanoparticles consisting of a mixture of several metals and also porous nanoparticles due to their special structure exhibit properties that find application in spectroscopic detection or catalysis. Abstract : Nanoparticles consisting of a mixture of several metals and also porous nanoparticles due to their special structure exhibit properties that find applications in spectroscopic detection or catalysis. Different approaches of top down or bottom up technologies exist for the fabrication of such particles. We present a novel combined approach for the fabrication of spherical porous gold nanoparticles on low-cost glass substrates under ambient conditions using a UV-laser induced particle preparation process with subsequent wet chemical selective etching. In this preparation route, nanometer-sized branched structures are formed in spherical particles. The laser process, which is applied to a silver/gold bilayer system with different individual layer thicknesses, generates spherical mixed particles in a nanosecond range and influences the properties of the fabricated nanoparticles, such as the size and the mixture and thus the spectral response. The subsequent etching process is performed by selective wet chemical removal of silver from the nanoparticles with diluted nitric acid. The gold to silver ratio was investigated by energy-dispersive X-ray spectroscopy. The porosity depends on laser parameters and film thickness as well as on etching parameters such as time. After etching, the surface area of the remaining Au nanoparticles increases which makes these particles interesting for catalysis and also as carrier particles for substances. Such substances can be positioned at defined locations or be released in appropriate environments. Absorbance spectra are also analyzed to show how the altered fractured shape of the particles changes localized plasmon resonances of the resultingt particles.